A cement-based electrode supercapacitor with high capacitance and preparation method thereof

By regulating the positive and negative electrode materials of cement-based supercapacitors, the electrode adsorption ability to charge is improved, the problem of insufficient capacitance of existing cement-based supercapacitors is solved, and the capacitance is significantly improved, meeting the demand for high capacitance.

CN118737717BActive Publication Date: 2024-12-27SHANDONG UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410887643.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-03
Publication Date
2024-12-27
Estimated Expiration
2044-07-03

AI Technical Summary

Technical Problem

The capacitance of existing cement-based supercapacitors is not high, and only a few falas are difficult to meet the actual application needs.

Method used

By regulating the positive and negative electrode materials, the electrode can absorb positive and negative charges, including adding conductive carbon black, cement and potassium dihydrogen phosphate to the positive electrode, and using slag and ammonium chloride aqueous solution for decalcification in the negative electrode, improving the Charge storage capacity of the electrode.

Benefits of technology

The capacitance of supercapacitors has been improved, and the capacitance has been increased by more than 3 times, significantly improving the charge storage capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118737717B_ABST
    Figure CN118737717B_ABST
Patent Text Reader

Abstract

The present invention provides a cement-based electrode supercapacitor with high capacitance and a preparation method thereof, and relates to the technical field of supercapacitors. The negative electrode is treated as follows: 1) carbon black and slag are added to the formed cement-based material and cured; 2) the material is decalcified by soaking in an ammonium chloride solution. The positive electrode is treated as follows: carbon black, potassium dihydrogen phosphate, and calcium hydroxide are added to the formed cement-based material and cured. The present invention improves the adsorption capacity of the electrode material for positive and negative charges by respectively regulating the positive and negative electrode materials, thereby increasing the upper limit of the charge storage capacity of the electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of supercapacitors, and in particular to a cement-based electrode supercapacitor with high capacitance and a preparation method thereof. Background Art

[0002] Cement-based supercapacitors are basically supercapacitors with cement-based materials as electrolytes. Only one SCI academic paper (Carbon-cement supercapacitors as a scalable bulk energy storage solution) was published in the second half of last year, proposing a new solution to store electrical energy in cement - a carbon-cement supercapacitor based on cheap and easily available cement, water and carbon black. However, this supercapacitor has the problem of low capacitance, with a maximum specific capacitance of only a few farads. Summary of the invention

[0003] In order to solve the above problems, the present invention improves the adsorption capacity of the electrode material for positive and negative charges by respectively regulating the positive and negative electrode materials, thereby increasing the upper limit of the charge storage capacity of the electrode.

[0004] One of the objects of the present invention is to provide a cement-based electrode supercapacitor with high capacitance.

[0005] A second object of the present invention is to provide a method for preparing the cement-based electrode supercapacitor with high capacitance.

[0006] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0007] In a first aspect, the present invention provides a cement-based electrode supercapacitor with high capacitance, comprising a positive electrode and a negative electrode immersed in an electrolyte, wherein the positive electrode is prepared by the following method:

[0008] Conductive carbon black, cement, potassium dihydrogen phosphate and calcium hydroxide are mixed and stirred to obtain a dry mixture, and water and a water reducing agent are added, poured into a mold and vibrated, and after hardening and demoulding, placed in a standard curing environment for curing, and cut to obtain a positive electrode;

[0009] The negative electrode is prepared by the following method:

[0010] Conductive carbon black, cement and slag are mixed and stirred to obtain a dry mixture, and water and a water reducing agent are added, poured into a mold and vibrated, and after hardening and demolding, placed in a standard curing environment for curing and cutting; the cured negative electrode is placed in an ammonium chloride aqueous solution for soaking and decalcification, and the negative electrode is obtained after cleaning.

[0011] The following is a detailed description:

[0012] Cathode preparation:

[0013] The conductive carbon black can be one or more selected from acetylene black, SP, and Ketjen black. The specific surface area of ​​the conductive carbon black is 50 m 2 / g-1200m 2 / g;

[0014] The cement may be one or more selected from the group consisting of silicate cement, ordinary silicate cement, slag silicate cement, pozzolanic silicate cement, fly ash silicate cement, composite silicate cement, medium heat silicate cement, low heat slag silicate cement, and white silicate cement. The strength grade of the cement may be 425, 625, 325, 525, etc., without particular limitation.

[0015] In some embodiments, the mass of the conductive carbon black accounts for 8% to 13% of the total mass of the cement and potassium dihydrogen phosphate;

[0016] In some embodiments, the mass of potassium dihydrogen phosphate accounts for 5% to 20% of the total mass of cement and potassium dihydrogen phosphate.

[0017] In some embodiments, the mass of calcium hydroxide accounts for 5% to 10% of the total mass of cement and potassium dihydrogen phosphate.

[0018] The water reducing agent may be a polycarboxylic acid high efficiency water reducing agent.

[0019] In some embodiments, the water-cement ratio is 0.8-1.6, and the mass of the water reducer accounts for 0.2%-0.5% of the mass of water.

[0020] In some embodiments, the curing temperature is 20±2° C., and the relative humidity is controlled at above 95%.

[0021] In some embodiments, the positive electrode is obtained by cutting into thin sheets with a thickness of 1-20 mm and single-side polishing after cutting.

[0022] Positive electrode preparation mechanism: Potassium dihydrogen phosphate is rich in active P elements, which will dissolve in the reaction environment and can replace Si atoms in the main hydration products. This substitution process leads to an increase in local positive charge, which is beneficial to the adsorption of anions; calcium hydroxide has a positive zeta potential and tends to adsorb anions.

[0023] Negative electrode preparation:

[0024] The conductive carbon black can be one or more selected from acetylene black, SP, and Ketjen black. The specific surface area of ​​the conductive carbon black is 50 m 2 / g-1200m 2 / g;

[0025] The cement may be one or more selected from the group consisting of silicate cement, ordinary silicate cement, slag silicate cement, pozzolanic silicate cement, fly ash silicate cement, composite silicate cement, medium heat silicate cement, low heat slag silicate cement, and white silicate cement. The strength grade of the cement may be 425, 625, 325, 525, etc., without particular limitation.

[0026] The slag may be blast furnace ore powder (S105 grade), coal fly ash (primary ash) or metakaolin, and the average particle size is 0.1 μm to 100 μm.

[0027] In some embodiments, the mass of the conductive carbon black accounts for 8% to 13% of the total mass of the cement and slag;

[0028] In some embodiments, the mass of slag accounts for 4% to 40% of the total mass of cement and slag; blast furnace slag may account for 5% to 40%; fly ash or metakaolin may account for 5% to 20%.

[0029] The water reducing agent may be a polycarboxylic acid high efficiency water reducing agent.

[0030] In some embodiments, the water-cement ratio is 0.8-1.6, and the mass of the water reducer accounts for 0.2%-0.5% of the mass of water.

[0031] In some embodiments, the curing temperature is 20±2° C., and the relative humidity is controlled at above 95%.

[0032] In some embodiments, the film is cut into slices having a thickness of 1-20 mm.

[0033] In some embodiments, the concentration of the aqueous ammonium chloride solution is 0.5 to 1.5 mol / L; and the soaking time is 10 min to 24 h.

[0034] The degree of decalcification is controlled by controlling the concentration of the solution and the soaking time. After decalcification, the solution is cleaned through multiple washings.

[0035] Negative electrode preparation mechanism: slag is rich in active Al elements. When added to cement hydration, it is proven that it can depolymerize and dissolve in a strong alkaline environment and participate in the cement hydration reaction. It can replace Si atoms in the main hydration products. This substitution process leads to a decrease in local positive charge, which is beneficial to the adsorption of cations. Then, decalcification treatment is carried out to further significantly reduce the existing stock of cations in the electrode and increase the new adsorbable amount. In addition, the replacement of Al phase in slag strengthens the molecular skeleton structure of the main hydration product, increases chemical stability, and inhibits the chemical reaction response of the hydration product caused by decalcification (for example: silicon chain hydroxylation or silicon chain polymerization to neutralize the charge lost by Ca ions).

[0036] In some embodiments, the electrolyte is a 100 mmol / L to 1.5 mol / L potassium hydroxide aqueous solution.

[0037] In some embodiments, the cement-based electrode supercapacitor with high capacitance further comprises a glass fiber membrane between the positive electrode and the negative electrode, and conductive graphite paper on the surface of the positive electrode and the negative electrode. The glass fiber membrane has a thickness of 0.1-1 mm; the glass fiber membrane is also pre-impregnated with an electrolyte.

[0038] In a second aspect, the present invention provides a method for preparing the above-mentioned cement-based electrode supercapacitor with high capacitance, comprising the following steps:

[0039] Positive electrode preparation: Conductive carbon black, cement, potassium dihydrogen phosphate and calcium hydroxide are mixed and stirred to obtain a dry mixture, and water and a water reducing agent are added, poured into a mold and vibrated, and after hardening and demoulding, placed in a standard curing environment for curing, and cut to obtain a positive electrode;

[0040] Preparation of negative electrode: Conductive carbon black, cement and slag are mixed and stirred to obtain a dry mixture, and water and a water reducing agent are added, poured into a mold and vibrated, and after hardening and demoulding, placed in a standard curing environment for curing and cutting; the cured negative electrode is placed in an ammonium chloride aqueous solution for soaking and decalcification, and the negative electrode is obtained after cleaning;

[0041] Assembly: The positive electrode and the negative electrode are respectively immersed in the electrolyte until saturated, combined with the glass fiber membrane and conductive graphite paper, and packaged to obtain a cement-based electrode supercapacitor with high capacitance.

[0042] Graphite paper covers the electrodes, and wires extend from the conductive graphite paper.

[0043] The description of the raw materials in the second aspect is the same as that in the first aspect and will not be repeated here.

[0044] In some embodiments, in the preparation of the positive electrode, the mass of the conductive carbon black accounts for 8% to 13% of the total mass of the cement and potassium dihydrogen phosphate;

[0045] In some embodiments, during the preparation of the positive electrode, the mass of potassium dihydrogen phosphate accounts for 5% to 20% of the total mass of cement and potassium dihydrogen phosphate.

[0046] In some embodiments, in the preparation of the positive electrode, the mass of calcium hydroxide accounts for 5% to 10% of the total mass of cement and potassium dihydrogen phosphate.

[0047] In some embodiments, during the preparation of the positive electrode, the water-cement ratio is 0.8 to 1.6, and the mass of the water reducer accounts for 0.2% to 0.5% of the mass of water.

[0048] In some embodiments, during the preparation of the positive electrode, the curing temperature is 20±2° C. and the relative humidity is controlled at above 95%.

[0049] In some embodiments, during the preparation of the positive electrode, the positive electrode is cut into thin sheets with a thickness of 1-20 mm, and then single-sided polishing is performed after cutting to obtain the positive electrode.

[0050] In some embodiments, in the preparation of the negative electrode, the mass of the conductive carbon black accounts for 8% to 13% of the total mass of cement and slag;

[0051] In some embodiments, during the preparation of the negative electrode, the mass of slag accounts for 5% to 40% of the total mass of cement and slag.

[0052] In some embodiments, during the preparation of the negative electrode, the water-cement ratio is 0.8 to 1.6, and the mass of the water reducer accounts for 0.2% to 0.5% of the mass of water.

[0053] In some embodiments, during the preparation of the negative electrode, the curing temperature is 20±2° C. and the relative humidity is controlled at above 95%.

[0054] In some embodiments, during the preparation of the negative electrode, the negative electrode is cut into thin sheets with a thickness of 1-20 mm.

[0055] In some embodiments, during the preparation of the negative electrode, the concentration of the aqueous ammonium chloride solution is 0.5 to 1.5 mol / L, and the immersion time is 10 min to 24 h.

[0056] In some embodiments, the electrolyte is a 100mmol / L to 1.5mol / L potassium hydroxide aqueous solution; the glass fiber membrane has a thickness of 0.1-1mm; the conductive graphite paper has a thickness of 0.1-1mm; and a packaging device is used to apply prestress to the assembled capacitor to make it fit tightly.

[0057] Beneficial Effects

[0058] The present invention improves the adsorption capacity of the electrode materials for positive and negative charges by regulating the positive and negative electrode materials respectively, thereby increasing the upper limit of the charge storage capacity of the electrode and increasing the capacitance of the supercapacitor by more than 3 times.

[0059] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] Figure 1 The invention shows the principle of improving the charge storage capacity of the cement-based electrode in the supercapacitor and the schematic diagram of the supercapacitor structure;

[0061] Figure 2 The results of Example 1 at a current density of 5 mA / cm 2 The charge and discharge diagram below.

[0062] Diagram: 1-positive electrode; 2-glass fiber membrane; 3-negative electrode; 4-external wire; 5-conductive graphite paper. DETAILED DESCRIPTION

[0063] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.

[0064] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.

[0065] Constant current charge and discharge test (GCD) of supercapacitor:

[0066] The electrochemical performance test was carried out using a CHI760e electrochemical workstation. The electrode sheet and the diaphragm were immersed in the electrolyte for at least 12 hours before the test. The cut-off potential of the constant current charge-discharge method was 1V; the charging time was 10s; and the acquisition interval was 0.01. The scan rates of the voltammetry test were 120mV / s, 250mV / s, and 500mV / s, respectively, and the current density of the cross-current charge-discharge method was 30A / cm 2 , 50A / cm 2 , the number of charge and discharge cycles is 10 times.

[0067] Capacitance: Calculated by constant current charge and discharge test (GCD), the calculation formula is as follows:

[0068]

[0069] Where C is the capacitance, I is the constant current set by the GCD, t is the discharge time measured by the GCD, and V0 is the charge cut-off voltage set by the GCD.

[0070] The materials and equipment used in the embodiments are as follows:

[0071] Ketchen Black was purchased from Xinghua Kaizheng New Energy Materials Co., Ltd., with a specific surface area of ​​1132m 2 / g;

[0072] The slag was purchased from Shijiazhuang Yuanjing Mineral Products Co., Ltd. and was grade S105;

[0073] The fly ash was purchased from Hebei Zongrun Mineral Products Co., Ltd. and was first-grade fly ash;

[0074] Naphthalene-based high-efficiency water reducer was purchased from Jiangsu Subote New Materials Co., Ltd., model: -B.

[0075] Example 1

[0076] A cement-based electrode supercapacitor with high capacitance, such as Figure 1As shown, the specific steps are as follows:

[0077] Cathode preparation:

[0078] With a carbon black / cement + potassium dihydrogen phosphate mass ratio of 12.6%, take 1.2g of Ketjen black, 8g of 425# Portland cement, 1.5g of potassium dihydrogen phosphate, and 0.5g of calcium hydroxide, and stir the mixture for 20 minutes. The water-cement ratio is 1.5, and the mass of the water reducer is 0.5% of the mass of water. Pour the dry powder mixture and stir for 20 minutes until it is evenly mixed, pour it into a 2cm*2cm*3cm mold; place it on a vibrating table and vibrate it for 2 minutes. After hardening, demold it and place it in a curing box with a temperature of 20±2℃ and a relative humidity controlled at more than 95% for 28 days. Cut the cured positive electrode into 3mm thick slices, polish one side, and use ultrasonic cleaning to remove impurities in the pores.

[0079] Negative electrode preparation:

[0080] With a carbon black / cement+slag mass ratio of 12.5%, take 1.2g of Ketjen black, 6.72g of 425# Portland cement, and 2.88g of slag, and stir the above mixture for 20 minutes until it is evenly mixed. With a water-cement ratio of 1.5, the mass of the water reducer is 0.5% of the mass of water, pour in the dry powder mixture and stir for 20 minutes, pour into a 2cm*2cm*3cm mold; place it on a vibrating table and vibrate for 2 minutes. After hardening, demould it and place it in a curing box with a temperature of 20±2℃ and a relative humidity controlled at more than 95% for 28 days. After curing, cut it into 3mm thick slices, soak it in a 1mol / L ammonium chloride aqueous solution for 12 hours, then polish it on one side and use ultrasonic cleaning.

[0081] The positive and negative electrodes were placed in an electrolyte (1M potassium hydroxide aqueous solution) and soaked for 12 hours, and then combined with a 0.6 mm thick glass fiber membrane soaked in the electrolyte and a 1 mm thick conductive graphite paper to form a supercapacitor, which was finally packaged in a specific container to test the electrochemical performance.

[0082] The supercapacitor was tested by constant current charge and discharge method using CHI760e electrochemical workstation. Figure 2 As shown, it can be seen from the figure that it has a stable charging and discharging process, the discharge time is slightly less than the charging time, and the coulombic efficiency is greater than 80%, proving that the electrochemical performance is good.

[0083] Example 2

[0084] The operation was basically the same as in Example 1, except that 2.88 g of slag in the negative electrode was replaced with 1 g of fly ash and 1.88 g of slag.

[0085] Example 3

[0086] The operation is basically the same as that of Example 1, except that the mass of potassium dihydrogen phosphate used in the positive electrode is 1 g, and the mass of 425# silicate cement used is 8.5 g.

[0087] Comparative Example 1

[0088] The positive and negative electrodes are not subjected to the above treatment. Both positive and negative electrodes are made of carbon-cement-based materials. The production process is as follows:

[0089] With a carbon black / cement mass ratio of 12.5%, take 1.2g of Ketjen black and 9.6g of 425# Portland cement, and stir the mixture for 20 minutes until it is evenly mixed. With a water-cement ratio of 1.5, the mass of the water reducer is 0.5% of the mass of water, pour in the dry powder mixture and stir for 20 minutes, pour into a 2cm*2cm*3cm mold; place it on a vibrating table and vibrate for 2 minutes. After hardening, demould it and place it in a curing box with a temperature of 20±2℃ and a relative humidity controlled at more than 95% for 28 days. After curing, cut it into 3mm thick slices, polish it on one side, and use ultrasonic cleaning after cutting.

[0090] Comparative Example 2

[0091] The operation is basically the same as that of Example 1, but the positive electrode adopts that of Example 1 and the negative electrode adopts that of Comparative Example 1.

[0092] Comparative Example 3

[0093] The operation is basically the same as that of Example 1, but the negative electrode adopts that of Example 1 and the positive electrode adopts that of Comparative Example 1.

[0094] Comparative Example 4

[0095] The operation is basically the same as in Example 1, but no calcium hydroxide is added to the positive electrode.

[0096] Comparative Example 5

[0097] The operation is basically the same as that of Example 1, but the negative electrode is not immersed in an aqueous solution of ammonium chloride for decalcification.

[0098] The capacitance results of the embodiments and comparative examples are shown in the following table.

[0099] Test piece Capacitance(F / g) Example 1 9.5 Example 2 8.7 Example 3 8.1 Comparative Example 1 2.3 Comparative Example 2 2.9 Comparative Example 3 2.88 Comparative Example 4 7.9 Comparative Example 5 4.2

[0100] The above embodiments are only used to illustrate the technical solutions of the present invention, but not to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments can be modified, or some or all of the technical features can be replaced by equivalents without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.

Claims

1. A cement-based electrode supercapacitor with high capacitance, characterized in that: The invention comprises a positive electrode and a negative electrode immersed in an electrolyte, wherein the positive electrode is prepared by the following method: Conductive carbon black, cement, potassium dihydrogen phosphate and calcium hydroxide are mixed and stirred to obtain a dry mixture, and water and a water reducing agent are added, poured into a mold and vibrated, and after hardening and demoulding, placed in a standard curing environment for curing, and cut to obtain a positive electrode; The negative electrode is prepared by the following method: Conductive carbon black, cement and slag are mixed and stirred to obtain a dry mixture, and water and a water reducing agent are added, poured into a mold and vibrated, and after hardening and demolding, placed in a standard curing environment for curing and cutting; the cured negative electrode is placed in an ammonium chloride aqueous solution for soaking and decalcification, and the negative electrode is obtained after cleaning.

2. The cement-based electrode supercapacitor with high capacitance according to claim 1, characterized in that: In the preparation of the positive electrode and the negative electrode, the conductive carbon black is one or more selected from acetylene black, SP, and Ketjen black, and the specific surface area of ​​the conductive carbon black is 50m 2 / g-1200m 2 / g; The cement is one or more selected from the group consisting of silicate cement, ordinary silicate cement, slag silicate cement, pozzolanic silicate cement, fly ash silicate cement, composite silicate cement, medium heat silicate cement, low heat slag silicate cement, and white silicate cement; The water reducer is a polycarboxylic acid high efficiency water reducer.

3. The cement-based electrode supercapacitor with high capacitance according to claim 1, characterized in that: In the preparation of the positive electrode, the mass of the conductive carbon black accounts for 8% to 13% of the total mass of cement and potassium dihydrogen phosphate; The mass of potassium dihydrogen phosphate accounts for 5% to 20% of the total mass of cement and potassium dihydrogen phosphate; The mass of calcium hydroxide accounts for 5% to 10% of the total mass of cement and potassium dihydrogen phosphate; The water-cement ratio is 0.8-1.6, and the mass of the water reducer accounts for 0.2%-0.5% of the mass of water.

4. The cement-based electrode supercapacitor with high capacitance according to claim 1, characterized in that: In the preparation of the negative electrode, the slag is blast furnace ore powder, coal fly ash or metakaolin, and the average particle size is 0.1μm to 100μm.

5. The cement-based electrode supercapacitor with high capacitance according to claim 1, characterized in that: In the preparation of negative electrode, the mass of conductive carbon black accounts for 8% to 13% of the total mass of cement and slag; The mass of slag accounts for 5% to 40% of the total mass of cement and slag; The water-cement ratio is 0.8-1.6, and the mass of the water reducer accounts for 0.2%-0.5% of the mass of water.

6. The cement-based electrode supercapacitor with high capacitance according to claim 1, characterized in that: During the preparation of positive and negative electrodes, the curing temperature is 20±2°C and the relative humidity is controlled above 95%; Cut into slices with a thickness of 1-20 mm.

7. The cement-based electrode supercapacitor with high capacitance according to claim 1, characterized in that: In the preparation of the negative electrode, the concentration of the ammonium chloride aqueous solution is 0.5 to 1.5 mol / L; the immersion time is 10 min to 24 h.

8. A method for preparing a cement-based electrode supercapacitor with high capacitance according to any one of claims 1 to 7, characterized in that: The steps include: Positive electrode preparation: Conductive carbon black, cement, potassium dihydrogen phosphate and calcium hydroxide are mixed and stirred to obtain a dry mixture, and water and a water reducing agent are added, poured into a mold and vibrated, and after hardening and demoulding, placed in a standard curing environment for curing, and cut to obtain a positive electrode; Preparation of negative electrode: Conductive carbon black, cement and slag are mixed and stirred to obtain a dry mixture, and water and a water reducing agent are added, poured into a mold and vibrated, and after hardening and demoulding, placed in a standard curing environment for curing and cutting; the cured negative electrode is placed in an ammonium chloride aqueous solution for soaking and decalcification, and the negative electrode is obtained after cleaning; Assembly: The positive electrode and the negative electrode are soaked in the electrolyte respectively until saturated, combined with the glass fiber membrane and conductive graphite paper, and packaged to obtain a cement-based electrode supercapacitor with high capacitance.

9. The preparation method according to claim 8, characterized in that: In the preparation of the positive electrode, the mass of the conductive carbon black accounts for 8% to 13% of the total mass of cement and potassium dihydrogen phosphate; The mass of potassium dihydrogen phosphate accounts for 5% to 20% of the total mass of cement and potassium dihydrogen phosphate; The mass of calcium hydroxide accounts for 5% to 10% of the total mass of cement and potassium dihydrogen phosphate; The water-cement ratio is 0.8-1.6, and the mass of the water reducer accounts for 0.2%-0.5% of the mass of water; The curing temperature is 20±2℃ and the relative humidity is controlled above 95%; The thin slices are cut into 1-20 mm thick slices, and polished on one side after cutting to obtain the positive electrode.

10. The preparation method according to claim 8, characterized in that: In the preparation of negative electrode, the mass of conductive carbon black accounts for 8% to 13% of the total mass of cement and slag; The mass of slag accounts for 5% to 40% of the total mass of cement and slag; The water-cement ratio is 0.8-1.6, and the mass of the water reducer accounts for 0.2%-0.5% of the mass of water; The curing temperature is 20±2℃ and the relative humidity is controlled above 95%; Cut into slices with a thickness of 1-20 mm; The concentration of the ammonium chloride aqueous solution is 0.5-1.5 mol / L; the soaking time is 10 min-24 h.